PENGARUH UKURAN DEWAN DIREKSI DAN DEWAN KOMISARIS SERTA UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur Sektor Consumer Good yang Terdaftar di BEI Tahun 2010-2012) - Panky Pradana Sukandar; Rahardja Rahardja (Diponegoro Journal of Accounting, 2014)
The purpose of this research is to analyze how much influence the board of directors, board of commissioners, as well as the size of the company to the company's financial performance in the consumer goods sector manufacturing companies listed in Indonesia Stock Exchange. The factors examined in this study is the performance of the company as the dependent variable while the size of the board of directors, board size, and the size of the company as an independent variable.The sample consists of 98 companies listed in Indonesia Stock Exchange (IDX) and submit financial reports to Bapepam consistently in the period 2010-2012. The data used in this study are secondary data and selection of samples using purposive sampling method. The analytical tool used is multiple regression analysis to examine the effect of the size of the board of directors, board of commissioners, and the size of the company or the company's financial performance.As the results of the research indicate that the board of commissioners and the size of the company does not have a significant effect on CFROA or financial performance. While the board of directors has a significant influence on CFROA or financial performance.